2006
DOI: 10.1007/s00420-006-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of prevalence of health complaints among young competitive swimmers

Abstract: Swimmers exposed to chlorination by-products in both the water and air of indoor swimming pools experience frequent respiratory symptoms that could potentially be reduced by limiting exposure to these products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…2 In keeping with this hypothesis, Lévesque et al 46 found that younger swimmers have the highest level of exposure to chloramines in both the air and the water. In their study, the swimmers most exposed to chloramines revealed significantly more upper and lower respiratory symptoms.…”
Section: The Issue Of Baby Swimmingmentioning
confidence: 86%
“…2 In keeping with this hypothesis, Lévesque et al 46 found that younger swimmers have the highest level of exposure to chloramines in both the air and the water. In their study, the swimmers most exposed to chloramines revealed significantly more upper and lower respiratory symptoms.…”
Section: The Issue Of Baby Swimmingmentioning
confidence: 86%
“…It is also predicted that crowded modern adventure bath with waterfalls, water slides and bubble pools could generate higher trichloramine levels in the air (Hery et al 1995;Richardson et al 2010). There are still gaps in the knowledge about the health effects of trichloramine, but many studies suggests it as the most important cause for airway symptoms among employees and visitors (Massin et al 1998;Jacobs et al 2007; Levesque et al 2006). In addition, trichloramine induced occupational asthma has been reported (Thickett et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…All these water disinfection systems have appeared in recent decades as a counterpoint to chlorination but they have not managed to take over. This could be explained by three main reasons 1) chlorine's great disinfecting efficiency, 2) the great optimisation and cheap price of chlorination systems, with almost a century worth of research and development, and 3) the lack of knowledge and/or the uncertainty of using new systems [55].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Levesque et al [55] compared the prevalence of health problems in young swimmers and footballers and observed that the presence of respiratory symptoms as coughing, sore throat, sore eyes and outer ear otitis was greater in swimmers than in indoor soccer players. They concluded that the incidence of these symptoms could potentially be reduced by limiting exposure to chlorination by-products.…”
Section: Effects On Competition Swimmers Technical Staff and Operatomentioning
confidence: 99%